Guga : breaking the barbecue rules - Tosta, Gustavo (DK Publishing, a division of Penguin Random House LLC, 2023)
"A bold new cookbook from the most adventurous BBQ guru on YouTube. There are lots of barbecue gurus out there, but Guga (aka Gustavo Tosta) does it just a bit differently and bit more boldly. Through his popular Guga Foods YouTube channel, Guga teaches his fans how to make out-of-this-world barbecue, as well as incredible sides, sandwiches, tacos, sauces, and more. In Guga: Breaking the Barbecue Rules, Guga shows readers how to make traditional barbecue recipes like smoked brisket, Texas-style ribs, and steak, but he also adds his larger-than-life flair to recipes like picanha (a Brazilian specialty), Korean-style chicken wings, and sweet-and-spicy pork belly. In addition to barbecue recipes, this beautiful cookbook contains recipes for sides like smoked mac and cheese, Japanese potato salad, and elotes (grilled Mexican street corn), fried bacon bread knots, and even Brazilian deep-fried bananas. Guga will teach even the most seasoned barbecue connoisseurs some new tricks, and beginning enthusiasts will learn how to take barbecue to an entirely different level. This is not just another barbecue book!"--Publisher.